Extremely severe maternal morbidity. A current approximation. - Hernandez-Cabrera, Yoan (2023)
Extremely severe maternal morbidity is the condition used to refer to any woman who has a serious complication during pregnancy, childbirth or the puerperium that puts her life at risk and requires immediate attention in order to avoid death. An information search was carried out in the Pubmed, Scopus, Dialnet and Lilacs databases. A search strategy was applied using the terms: perinatal care, postpartum hemorrhage, Near miss, maternal mortality. Of the 33 articles initially obtained, 30 met the inclusion criteria. Objective: To describe aspects related to extremely severe maternal morbidity that allow establishing health actions aimed at reducing maternal-perinatal complications and consequently maternal mortality.Postpartum hemorrhage and hypertensive disease of pregnancy continue to be the main causes of extremely severe maternal morbidity today, which varies according to the criteria used to define cases and the characteristics of the populations studied in different regions of the world. Added to this are predisposing factors such as: age over 34 years, previous history of postpartum hemorrhage, multiple pregnancy, hypertension, emergency cesarean section, anemia, lack of prenatal care, patients with previous abortions, and deliveries performed by poorly trained people. When describing the extremely severe maternal morbidity as an indicator that evaluates maternal health and the quality of care, there will be enough elements to identify these cases and make decisions regarding the implementation of more effective programs that allow the reduction of the maternal mortality.